Kütüphaneler ve müzelerde salgın hastalıklar ve erişim - GÜNEŞ, GÜSSÜN (My University, 2022)
Humans are living organisms that live in a harmony with their environment. When we look at the nature all living things are compatible with each other and depended one another. A healty person continous to live a healty life by integrating with their environment. Libraries and museums are cultural memory institutions that support education, social and cultural life within the scope of lifelong learning. These institutions which become a bridge between society’s past and the future will keep continue to their missions as places that protected sources of knowledge and transmitted to the future. There are many factors that effect the health of the society. Health and illness expresses that being in a good conditions of society in terms of physically and mentally as quality of life. The Covid-19 not only affected public health, but also affected behaviors of library users and musuem visitors. Epidemics which occured in society have changed all areas of life, regardless of the economic and social status. The pandemic isolations which aimed to protect public health interrupted socialization and people who became lonelier was taught or forced to learn what they can do. Also some changes occured in social life and culture of art and travel. As an example to this, it has experinced that a shell change in order to reach museum users. This experinced forced change caused to increase of using technology in libraries and museum services. Technology has become the most important element in terms of sociological, culturel and intellectually connecting people during the pandemic. Distance education processes, electronic commerce, virtual libraries and museums have enabled the reopening of the physical world from the virtual universe, allowing the digital culture to settle in the society. During the mandatory closure period, it provided people with access to the virtual library and museum, providing access to information and digital socialization. Within the scope of this study, the effects of pandemic diseases that have occured in societies from past to the present in libraries and museum were examined chronologicaly. Also changing services and newly developed services in the digital environment with the Covid-19 pandemic were evaluated.

İnsan çevresi ile uyum gösteren bir bütünsellik içinde yaşayan bir canlıdır. Doğaya bakıldığında bütün canlılar, her şey birbiriyle uyumlu ve birbirine bağımlıdır. Sağlıklı bir insan sağlıklı bir yaşantıya, sağlıklı bir çevreye ile bütünleşerek yaşamını sürdürür. Yaşam boyu öğrenme kapsamında kütüphaneler ve müzeler eğitimi, sosyal ve kültürel yaşamı destekleyen kültürel bellek kurumlarıdır. Toplumun geçmişi ile geleceği arasında kültürel bir köprü olan bu kurumlar kültürün taşıyıcısı olan bilgi kaynağının, korunduğu ve geleceğe aktarıldığı sosyal ve kültürel mekanlar olarak işlevlerini devam ettirmektedirler. Toplumun sağlığını etkileyen pek çok unsur bulunmaktadır. Sağlık ve hastalık toplumun yaşam kalitesine yönelik olarak bedensel, ruhsal ve fiziksel iyilik içinde olması durumu ifade etmektedir. Tüm dünyayı etkileyen Covid-19 salgını toplum sağlığını etkilediği kadar kütüphane okuyucuları ve kullanıcıları ile müze kullanıcı ve ziyaretçilerinin davranışlarını da etkilemiştir. Toplumda meydana gelen salgınlar ekonomik ve sosyal statünün derecesine bakılmaksızın yaşamın tüm alanları değiştirmiştir. Salgınlarda bireyin sağlığının korunma sürecinde zorunlu izolasyon giren ve sosyalleşmeyi kesintiye uğratan salgın yalnızlaşmayla insanın neler yapabileceğini öğretmiş ya da öğrenmek zorunda bırakılmıştır. Sosyal yaşamda sanat ve gezi kültüründe de değişim yaşanmıştır. Buna örnek olarak müze ve müze kullanıcılarına ulaşmak içinde kabuk değişimi geçirmiştir. Yaşanılan zorunlu değişim teknolojinin önemini artırıp, kütüphane ve müzeye yansımıştır. Teknoloji dünyada yaşanılan bu salgında insanların sosyolojik, kültürel ve entelektüel anlamda hayata bağlayan en önemli unsur olmuştur. Uzaktan eğitim süreçleri, elektronik ticaret, sanal kütüphaneler ve müzeler kapanan fiziksel dünyanın sanal evrenden yeniden açılmasını sağlayarak dijital kültürün toplumda yerleşmesini sağlamıştır. Zorunlu kapanma döneminde insanlara Sanal Kütüphane ve Müze erişim imkanları sağlayarak bilgiye erişim ve dijital sosyalleşme imkanı sunmuştur. Bu çalışma kapsamında geçmişten günümüze toplumlarda oluşan salgın hastalıkların kütüphane ve müzelerde etkisi kronolojik olarak incelenmiş, Covid-19 pandemisi ile günümüzde değişen hizmet yapıları ve dijital ortamdaki yeni nesil hizmet süreçleri değerlendirilmiştir.
Epidemic diseases in librarıes and museums & access
Keywords: Sosyal ve Beşeri Bilimler; Sağlık Bilimleri; Social Sciences and Humanities; Health Sciences; Klinik Tıp (MED); Sosyal Bilimler (SOC); Clinical Medicine (MED); Social Sciences (SOC)